Հայոց եկեղեցու փոխհարաբերությունները Բյուզանդիայի և Մերձավոր Արեւելքի եկեղեցական կենտրոնների հետ - Բոզոյան, Ազատ
In his time John (Hovhannes) of Odzun (d. 728) proclaimmed that the hierarchical structure, theological conceptions and the rite of the Armenian Church were inherited from the time of the apostles. Along with the restoration of the public institutions in the Bagratid period (880s-1045), the Armenian authorities granted vast privileges to the Church, which turned into the most influential leverage for maintaining the inner and foreign policy of the state. In order to shatter the Bagratid Kingdom, the Byzantine Empire resorted to inciting conflicts between the Chalcedonian and anti-Chalcedonian Churches. Trying to subjugate Armenians and their territories at any cost, the Byzantine emperors weakened the religious structure of the Armenian Church. With the Seljuq raids of the 11th century we see that policy of Byzantium led to the Byzantine secession of the Minor Asian provinces where the Iconian Sultanate (or Sultanate of Rum, 1077-1308) and the Danishmandid State (1104-1178) were created by the Seljuq Turks. This continued with the gradual loss of the entire Minor Asian holdings of the Byzantine Empire and the emergence of the Ottoman Empire over the Byzantine territory. Finally the capital Constantinople was taken in 1453. The history of Armenian-Byzantine church relations shows that the mentioned churches had multifaceted religious and cultural relations. Over the centuries, they have made attempts to settle religious differences. In the process, each of them created a unique culture and civil system, the study of which allows us to understand their role in the modern world. To understand the characteristics of these cultures, detailed studies of ecclesiastical and literary monuments are assumed.
Keywords: Հայոց եկեղեցի; Միջեկեղեցական հարաբերություններ